Hey there!
We can set up a system of equations. Since the two side lengths are equal, that means that (2x + 6) is equal to y, so:
2x + 6 = y
Next, we know that angles of a triangle add up to 180°, so:
2x + 6 + y + 5x - 12 = 180
Let's simplify this:
7x - 6 + y = `80
Now we have a system:
2x + 6 = y
7x - 6 + y = `80
We can solve using elimination, so we will subtract y from both sides in the first equation:
2x + 6 - y = 0
Now we can add them together:
9x = 80
So divide both sides by 9 and get:
8 8/9
Now, we can plug x in to an equation and solve for y
2(8 8/9) + 6 = y
17 7/9 + 6 = y
23 7/9 = y
Therefore, x = 8 8/9 and y = 23 7/9
Hope it helps and tell me if I'm mistaken. Have a good day!